1987
DOI: 10.1128/jb.169.9.4190-4195.1987
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of three proteins from the first gene of the RNA polymerase sigma 43 operon of Bacillus subtilis

Abstract: The first gene of the Bacillus subtilis RNA polymerase r43 operon, P23, has a protein-coding capacity of 23,000 daltons. Sequence analysis revealed three potential translational initiation sites within the same reading frame, which could encode proteins of 23,000 (P23), 19,000 (P19), and 9,000 (P9) daltons, respectively. An internal promoter (P3), which is expressed only during the sporulation stage, is located between the second and the third translational start sites. By protein fusion to the Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1988
1988
1991
1991

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…However, the relationships between growth, cell division, and sporulation are well established (4,8,17,25,30). In addition, we have found that two sporulation mutants (spoOB and spoOE) of B. subtilis are apparently defective in the tumover of the methyl group(s) on P-40 (K. J.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the relationships between growth, cell division, and sporulation are well established (4,8,17,25,30). In addition, we have found that two sporulation mutants (spoOB and spoOE) of B. subtilis are apparently defective in the tumover of the methyl group(s) on P-40 (K. J.…”
Section: Discussionmentioning
confidence: 86%
“…Sporulation is initiated in bacilli during the last generation of growth (4,24) and is characterized by a cascade of sigma factors or transcriptional regulators or both, but the mechanism by which this cascade is initiated is unknown (16,17,30,31). The regulation of these early events in sporulation is under the control of a set of genes (the spoO genes in Bacillus subtilis) whose products have not been characterized, although at least one (SpoOH) is thought to be a sigma factor (7).…”
mentioning
confidence: 99%
“…Swarm plates were spotted with fresh bacterial colonies and incubated at room (29). The filters were probed with antisera directed against sheared B. subtilis flagella.…”
Section: Methodsmentioning
confidence: 99%
“…The results of Wang and Doi (13) suggested that three polypeptides were produced from the P23 gene when the products were expressed as fusion proteins to 3-galactosidase from plasmids in B. subtilis and E. coli. Their results indicated that these polypeptides were all in the same phase and so would share the same C-terminal amino acids.…”
mentioning
confidence: 99%